Ways Of Rational Use Of Natural Resources Of The Molguzar Ridge - Bahoroy Yigitova; Nilufar Samatova (International Scientific and Current Research Conferences, 2020)
This article provides recommendations and comments on the use of natural resources of the Molguzar ridge in various sectors of the economy with a comprehensive study.